Efficacy of the Use of Balloon Tamponade through Foleys Catheter in the Arresting of Primary Post-Partum Haemorrhage Due to Atonic Uterus in Primary versus Multigravida - Momin, Nazish; Perveiz, Khwaja Fawad; Iqbal, Aniqa (Indus Journal of Bioscience Research, 2025)
Background: Primary postpartum hemorrhage is a major reason for maternity morbidity and mortality, and this is most common in resource-constrained environments. Uterine atony is the most prevalent cause of such cases. When there is failure of medical therapy, balloon tamponade using a Foley catheter is the most cost-effective solution to the problem. Objective: To determine the efficacy of balloon tamponade through Foley catheter in arresting primary postpartum hemorrhage due to atonic uterus and to compare outcomes between primigravida and multigravida women. Study Design: Observational cross sectional study. Duration and Place of Study: This study was conducted from February 2024 to August 2024 in the Department of Obstetrics and Gynecology, Lady Reading Hospital, Peshawar. Methodology: A total of 102 women aged 18 to 40 years presenting with primary postpartum hemorrhage due to uterine atony were included. Balloon tamponade was performed using Foley catheter inflated with sterile normal saline. Patients were followed for 24 hours. Efficacy was defined as complete arrest of bleeding without surgical intervention. Data were analyzed using Statistical Package for Social Sciences version 26. Comparison of efficacy between primigravida and multigravida was done using chi square test and Fisher exact test. A p value of ≤0.05 was considered significant. Results: Mean age was 28.40 ± 6.27 years. Overall efficacy was observed in 90 patients (88.20%). Efficacy was higher in primigravida women (93.8%) compared to multigravida women (83.3%) but the difference was not statistically significant (p = 0.130). Conclusion: Balloon tamponade through Foley catheter is an effective and safe method for managing primary postpartum hemorrhage due to uterine atony regardless of parity.